Tingkat Pengetahuan Konsumen Tentang Label Halal Pada Kosmetika dan Obat Herbal Terhadap Keputusan Pembelian Di Marketplace Online - Ayunanda Risetyaningsih; Azarine Daffa Azalia; Angelica Kresnamurti (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
Halal label is a sign of product halal status. Label halal is required to include in products that have received halal certification. Among the products that are required to carried a halal label are cosmetics and herbal medicines. Law number 42 of 2024 issued by government Indonesia concerning guanranteed halal products, that not all products in Indonesia are guaranteed to be halal. The regulation also states that Indonesia is obligade to provide protection and guarantees regarding halal status of product consume and used by the public. Cosmetic and herbal medicine are the products that musch used by the indonesian public. According to the survey, make-up and personal care ranked fourth (16.4%) as the most frequently purchased item by respondents when shopping online in 2022. In this current modern era, there has been shift in the way consumer purchase products. Purchases are No. longer made offline bu go to direct stores, instead buyers and sellers transact through digital platform (e-commerce) rather than meeting face to face. Before deciding to purchase a product, consumer have several consideration in choosing product, whether is jeeds, desires or whether is influenced by external factors. This study aims to determine whether consumer knowledge regarding halal labels on cosmetic and herbal medicine products influence purchasing decisions through e-commerce. The method used is quantitative descriptive, data collection through questionnaires. Data analysis used linear regression. The number of respondents was 100 people who had purchased cosmetic or herbal medicine products in online marketplaces domiciled in Surabaya. Data analysis shows that consumer knowledge regarding halal labels influences consumer purchasing decisions in online marketplaces, meaning that increasing consumer knowledge regarding halal labels will increase product purchases in online marketplaces.